Effects of water deficit and nitrogen application on leaf gas exchange, phytohormone signaling, biomass and water use efficiency of oat plants. Issue 6 (1st October 2020) - Li, Li; Ma, Haiyang; Xing, Jiayi; Liu, Fulai; Wang, Yaosheng
Abstract: Background : Water and nitrogen (N) are essential resources influencing plant growth and yield. To improve their efficiencies in crop production is challenging because the physiological mechanisms of water and N coupling and their interactive effect on crop water use efficiency (WUE) are not well understood yet. Aim : The aim of this study was to investigate the physiological responses and phytohormones signaling in oats in response to soil water status and N supply under fertigation, to explore the mechanisms regulating plant growth and WUE. Methods : Oat plants were subjected to the factorial combination of three soil moisture regimes (50, 70, and 90% of soil water holding capacity, SWHC) and three N levels (fertilized with 74, 149, and 298 mg kg −1 ). Results : The stomatal conductance (gs ) was significantly decreased by soil water deficit, and also by the highest N level, whereas photosynthesis rate (An ) was unaffected by neither water nor N. Consequently, intrinsic WUE (WUEint, An /gs ) was highest under reduced irrigation and high N fertilization. This effect at stomatal level was affirmed by responses in whole plant WUE (WUEb ), which was positively correlated with shoot δ 13 C. A positive correlation between δ 18 O and δ 13 C in shoots further indicated that decreases of gs rather than changes in An contributed to the enhanced WUE. Conclusion : Moderate soil water deficit and sufficient N supply is recommended for saving irrigation water and improving WUE on fertigated oat plants without compromising biomass accumulation to any large extent.